Modeling of the photocatalytic degradation reactions of aromatic pollutants: A solvent effect model - Kilic, Murat; San, Nevim; Cinar, Zekiye (WALTER DE GRUYTER GMBH, 2007)
The photocatalytic degradation reaction of 1,3-dihydroxybenzene has been modeled theoretically. With the intention of predicting the primary intermediates and the product distribution, geometry optimizations of the reactants, the product radicals and transition state complexes have been performed with the semi-empirical PM3 method. The molecular orbital calculations have been carried out by an SCF method using RHF or UHF formalisms. Solvation effects have been computed by DFT calculations at the B3LYP/6-31G* level using COSMO as the solvation model. Based on the results of the quantum mechanical calculations, the rate constants of the four possible reaction paths have been calculated by means of Transition state Theory. Three predictors have been determined for the prediction of the most probable transition state and the reaction path. A branching ratio for each of the reaction paths has been calculated and the most probable intermediate has been determined. Finally, the results obtained have been compared to the experimental results in order to assess the reliability of the proposed model.
Keywords: photocatalytic degradation; hydroxyl radicals; dihydroxybenzenes; DFF calculations; COSMO; SEMIEMPIRICAL METHODS; WATER-PURIFICATION; PHENOL; PHOTOOXIDATION; HYDROXYLATION; OPTIMIZATION; SUSPENSIONS; PARAMETERS; RADICALS; Chemistry